Pressure-Shear Crack Initiation and Expansion Mechanism of Complex Cracked Rock Mass under the Seepage Stress - Lu Shen (Advances in Civil Engineering)
This work was to analyze and discuss the propagation mechanism of compressive shear initiation of complex fractured rock mass with seepage stress. The dense marble of Daye Iron mine with bulk density of 26.6 kN/m3 and uniaxial compressive strength of 52.4 MPa was selected as the material, and the upper and lower fracture surfaces were polished smoothly. The crack initiation criterion under compressive shear stress state is analyzed by taking the theory of fracture mechanics and classical mechanics. The coupling equation in the extended finite element simulation is established. The influence of lateral pressure on the crack propagation law, the relationship between lateral pressure and fracture, the initial expansion angle and pressure change law, and the effect of working face length on the crack expansion are analyzed. Results. The initial expansion angle of cracks increases with the increase of lateral pressure, and that of a single crack decreases with the increase of pressure. When other conditions are constant, the crack angle of the crevice also shows a trend of increasing with the increase of lateral pressure. When the lateral pressure becomes smaller, the initial expansion angle is relatively small. With the progress of the step size, the expansion angle shows a gradually decreasing trend, that is, the initial expansion angle gradually decreases with the increase of water pressure. The smaller the working face length, the smaller the expansion length of the floor crack. Conclusion. The expansion of the floor cracks is mainly formed by the tensile shear failure, and the fracture water pressure will reduce the initiation stress, which makes the rock mass more prone to the fracture failure.